The Effectiveness of Practical Teaching of NFE Courses on the Placement Students at the NFE Partner Institutions - Bahar, Aswandi; Maemunaty, Titi; Alvi, Ria Rizkia (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to determine the effectiveness level of Practical Teaching of NFE courses on the placement students in the partner institutions. This research uses quantitative approach with descriptive analysis. The population in this study were students who had taken the 2014 class of non-formal education Teaching Practice courses at the University of Riau as many as 58 people. Sampling used is simple random sampling, the sample is 37 students. The instrument used is a questionnaire. Instrument validity uses product moment. Reliability calculation used Alpha formula. The quantitative data were analyzed quantitative descriptive in terms of percentages. The results showed that the level of effectiveness of practical Teaching of NFE subject to placement students in NFE partner institutions was moderate with indicators: 1) input obtained percentage value of 38.91% 2) process obtained percentage value of 49.05% 3) output obtained the percentage value of 55.41% 4) the outcome obtained by the percentage value of 54.04%. Thus, the level of effectiveness of Practical Teaching of NFE subject to placement of students in the NFE partner institutions is good although there are still many improvements that need to be done by Practical Teaching lecturers in order to provide benefits for students, universities and society.